Case Report: Recurrent Surgical Wound Dehiscence in a Patient With Surgical Site Infection, Type 2 Diabetes, and Obesity - Yogaswara, Hilman Ares; Sukarsa, Mochamad Rizkar Arev; Rachmawati, Anita (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Introduction: Surgical site infection (SSI) is the most likely complication following a Cesarean section (CS). SSI is considered a contributing factor to the occurrence of surgical wound dehiscence (SWD). This condition is often associated with various risk factors, such as type 2 diabetes mellitus (T2DM) and obesity. Understanding the risk factors and management of SWD in high-risk populations is essential for improving clinical outcomes.Case Report: A 27-year-old woman, G2P2A0, was referred due to SWD. The patient underwent a CS at a secondary-level hospital due to oxytocin drip failure 20 days prior to referral. She was diagnosed with SSI six days post-surgery, and had received antibiotics and undergone re-hecting 11 days after the CS. The surgical wound reopened two days after the re-hecting procedure, prompting referral. The patient had uncontrolled T2DM and morbid obesity as comorbidities. Physical examination revealed an open CS wound measuring 15x5x3 cm with exposed fascia and discharge of pus and blood. Wound care was performed using gauze coated with antibiotics changed every 12 hours. Antibiotic administration was based on culture, sensitivity, and resistance testing before another re-hecting procedure was performed.Conclusion: Obesity and diabetes mellitus were risk factors for SWD in this case. The use of antibiotics guided by culture sensitivity and resistance testing, effective SSI management, and early detection and management of comorbid conditions are necessary to prevent and treat SWD complications.Laporan Kasus: Recurrent Surgical Wound Dehiscence pada Pasien Infeksi Daerah Operasi yang Memiliki Komorbid Diabetes Tipe 2 dan ObesitasAbstrakLatar belakang: Infeksi Daerah Operasi (IDO) merupakan komplikasi yang paling mungkin terjadi setelah operasi Caesar (SC). IDO dianggap sebagai faktor terjadinya Surgical Wound Dehiscence (SWD). Kondisi ini sering dikaitkan dengan berbagai faktor risiko seperti diabetes melitus tipe 2 (DMT2) dan obesitas. Pemahaman mengenai faktor risiko dan penanganan SWD pada populasi berisiko tinggi menjadi penting untuk meningkatkan luaran klinis.Laporan Kasus: Wanita 27 tahun, P2A0, dirujuk karena SWD. Pasien menjalani SC di RS PPK tingkat II karena gagal drip oksitosin 20 hari sebelum dirujuk. Pasien didiagnosis IDO 6 hari setelah operasi dan telah mendapatkan antibiotik dan dilakukan re-hecting 11 hari setelah SC. Luka operasi terbuka kembali dua hari setelah re-hecting, sehingga pasien dirujuk. Pasien memiliki komorbid DMT2 tidak terkontrol dan obesitas morbid. Pemeriksaan fisik menunjukkan tampak luka bekas SC terbuka berukuran 15x5x3 cm dengan dasar fasia dengan nanah dan darah. Perawatan luka dilakukan dengan kasa dilapisi antibiotik dan diganti setiap 12 jam. Antibiotik diberikan berdasarkan hasil tes kultur, sensitivitas, dan resistensi, sebelum dilakukan re-hecting kembali. Kesimpulan: Obesitas dan diabetes melitus menjadi faktor risiko terjadinya SWD pada kasus ini. Penggunaan antibiotik sesuai hasil kultur sensitivitas dan resistensi, perawatan IDO, serta deteksi dan manajemen faktor komorbid diperlukan untuk mencegah dan mengobati komplikasi SWD.Kata kunci: Diabetes mellitus tipe 2, infeksi daerah operasi, luka operasi terbuka, rekurensi